Protein oxidation affects proteolysis in a meat model system. (August 2015) - Berardo, Alberto; Claeys, Erik; Vossen, Els; Leroy, Frédéric; De Smet, Stefaan
Abstract: The effect of hydrogen peroxide-induced protein oxidation and pH (4.8 and 5.2) on meat proteolysis was investigated in a meat model system for dry fermented sausages. In oxidised samples, increased protein carbonyl contents and decreased thiol concentrations were found. The initial concentration of protein carbonyls was significantly lower in oxidised samples at pH 4.8 than in ones at pH 5.2, but after ten days comparable levels were reached. The inhibition of proteolysis by the addition of a protease inhibitor cocktail did not influence protein oxidation. Yet, proteolysis was negatively affected by low pH values as well as by oxidation, resulting in a reduced release of amino acids during ripening. Highlights: The effect of protein oxidation and pH on proteolysis and vice-versa was tested. Severe protein oxidation impairs proteolysis in fermented sausages. Proteolysis does not affect protein oxidation. A lower pH reduces the amino acid release during meat fermentation.